Acute disseminated encephalomyelitis presenting as a solitary brainstem mass. Issue 8 (August 1993) - Miller, D H; Scaravilli, F; Thomas, D C; Harvey, P; Hirsch, N P
Abstract : A 36 year old woman presented with a subacute brainstem syndrome. MRI showed a solitary, gadolinium enhancing brainstem mass, which on biopsy showed perivenous inflammation and demyelination compatible with acute disseminated encephalomyelitis.